“Humanly Possible”: Geographies, Metrics and Methods to Address Immunization Inequalities - Nambiar, Devaki; Hosseinpoor, Ahmad Reza; Bergen, Nicole; Danovaro-Holliday, M. Carolina; Sugerman, Ciara E.; Johnson, Hope L. (Vaccines (Basel), 2024)
The year 2024 marks the 50th anniversary of the World Health Organization (WHO) Expanded Program on Immunization (EPI) [...].The year 2024 marks the 50th anniversary of the World Health Organization (WHO) Expanded Program on Immunization (EPI) [...].